2018
DOI: 10.31788/rjc.2018.1133084
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Sulfonylurea-Linked Chalconoids as Antidiabetic Agents: Evaluation of Antihyperglycemic Effects in Streptozotocininduced Type 2 Diabetic Rats

Abstract: The proposed investigation was carried out to evaluate the antihyperglycemic potential and to explore the structureactivity relationship (SAR) of a series of 28 hybrid sulfonylurea-linked chalconoids using streptozotocin-induced type 2 diabetic rats. Among all the compounds tested, compound SC 21 exhibited remarkable antidiabetic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Several authors have evaluated the antihyperglycemic activity of synthetic chalcones in streptozotocin-induced diabetic rats ( Satyanarayana et al, 2004 ; Shukla et al, 2007 ; Najafian et al, 2010 ; Rawat et al, 2011 ; Mahapatra et al, 2017a ; Sengupta et al, 2017 ; Shukla et al, 2017 ; Tajammal et al, 2017 ; Acharjee et al, 2018 ; Naidu, 2018 ; Raju et al, 2018 ). It was found that these compounds have a moderate to potential ability to reduce blood sugar.…”
Section: Preclinical Pharmacological Activities Of Chalconesmentioning
confidence: 99%
“…Several authors have evaluated the antihyperglycemic activity of synthetic chalcones in streptozotocin-induced diabetic rats ( Satyanarayana et al, 2004 ; Shukla et al, 2007 ; Najafian et al, 2010 ; Rawat et al, 2011 ; Mahapatra et al, 2017a ; Sengupta et al, 2017 ; Shukla et al, 2017 ; Tajammal et al, 2017 ; Acharjee et al, 2018 ; Naidu, 2018 ; Raju et al, 2018 ). It was found that these compounds have a moderate to potential ability to reduce blood sugar.…”
Section: Preclinical Pharmacological Activities Of Chalconesmentioning
confidence: 99%